2006
DOI: 10.2174/157018006775240917
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of Structure-Activity Relationship of Cytotoxic Physalins

Abstract: Physalins D (1), B (2), F (3), 5α-ethoxy-6β-hydroxy-5,6-dihydrophysalin B (4) and E (5), all isolated from Physalis angulata L. extracts, were tested for cytotoxic activity using a panel of tumor cell lines and sea urchin eggs. In general, the most active compounds were 1 and 3, followed by 2 and 4. Compound 4a obtained by the hydrogenation of 4 was weaker than all the others in tumor cells and possessed no activity in sea urchin eggs. Compound 5 had no activity in tumor cells and exhibited activity in sea urc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Among the physalins, physalins B (463), D (313), F (450), and H (312) showed strong cytotoxicity against multiple tumor cell lines, while physalins G (314), I (510), and physanolide A (367) were inactive. Physalins J (457) and U (304) were marginally active (55,134,146,244,245). The 18-nor-physalin, withaphysanolide A (438), also was weakly active (186).…”
Section: Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Among the physalins, physalins B (463), D (313), F (450), and H (312) showed strong cytotoxicity against multiple tumor cell lines, while physalins G (314), I (510), and physanolide A (367) were inactive. Physalins J (457) and U (304) were marginally active (55,134,146,244,245). The 18-nor-physalin, withaphysanolide A (438), also was weakly active (186).…”
Section: Cytotoxicitymentioning
confidence: 99%
“…However, as already mentioned in Sect. 5.2.3., the structure of physalin E was incorrectly assigned and later shown to be identical to physalin D (313) (244). Accordingly, these bioactivity results should be considered with caution.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…In fact, it seems that structure requirements for cytotoxicity are far from being established. Recent studies with physalins, another group of withasteroids, suggested that the cytotoxicity is probably determined by the combination of the conjugated cyclohexenone moiety and the presence of oxygens located at both C-5 and C-6 (Lee and Houghton, 2005;Magalhães et al, 2006). Thus, the oxygenation of C-5 and C-6, and probably, an ethoxy group at C-18, seem to be important for withaphysalin cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical: seco-steroids (physalins) (Soares et al, 2006;Abe et al, 2006;Kuo et al, 2006;Magalhães et al, 2006a;Magalhães et al, 2006b;Damu et al, 2007), alkaloids (Edeoga et al, 2005), tannins and flavonoids (Edeoga et al, 2005;Wollenweber et al, 2005), the withanolides withangulatin (Lee et al, 2008) and physagulins . Patents that were reported, both in the European Patent Office and the Brazilian National Institute of industrial Property databases, most of which concern inflammatory, allergic, parasitic, infectious or digestive diseases, including extracts from P. angulata (Balbani et al, 2009 (Zakaria et al, 2006); can cause a central nervous system depression which may be correlated with an increased parasympathetic tone (Perez et al, 1998), antioxidant (Al-Fatimi et al, 2007); antipyretic and anticancer agent (Hsieh et al, 2008;Hsu et al, 2009;Yang et al, 2010;Li et al, 2008;Li et al, 2009), mutagenic activity (Almeida et al, 2010).…”
Section: Plants From Solanaceae Family With Possible Anxiolytic Effecmentioning
confidence: 99%